The Influence Of Product Diversity, Product Quality And Distribution Channels On Customer Loyalty At PT Pan Baruna Batam - Fernandi Fernandi; Yunisa Oktavia (STIE Amkop Makassar, 2024)
This research was conducted to find out the effect of product diversity, product quality and distribution channels on customer loyalty where each variable has problems such as expiration, torn packaging and excess and shortage of stock. So this type of research is quantitative research to test the relationship between hypothesized variables. This research has a population with the number of PT Pan Baruna customers in 2023, namely 826 customers from PT Pan Baruna marketing. This research uses a purposive sampling method. The results of this research show that the variables of product diversity, product quality and distribution channels are significantly positive on customer loyalty.